La difficile prise en compte de l’expérience spatiale des élèves dans l’enseignement de la géographie au cycle 3 de l’école primaire - Benoit Bunnik (Éducation et Socialisation)
Taking into account the spatial experience of students in geography in CM1 and CM2 makes it possible to start from the lived and practiced daily lives of students to enable them to understand their role as spatial actors in a complex world. This is one of the demands of the current school program. However, a large proportion of primary school teachers1 have difficulty integrating this consideration of experience into their teaching. This article aims to show and understand the gap that exists between the prescribed curriculum and the real curriculum based on the representations of teachers interviewed during the summer of 2021. If the spatial experience of students is thought of as a relevant tool, it enters with difficulty into the classroom practices of teachers who are dominated by the idea that geography is a discipline of distancing from the world in which we learn little to understand the role of spatial actors, including that of students, in the construction of the contemporary world.